Acute Submandibular Sialadenitis-A Case Report - Rakhi Chandak; Shirish Degwekar; Manoj Chandak; Shivlal Rawlani (Hindawi Limited, 2012)
Many conditions affect the salivary glands. Acute sialadenitis is infectious or inflammatory disorders of the salivary glands. The exact frequency of submandibular sialadenitis is unclear. The acute conditions more typically involve the parotid and submandibular glands. During an acute inflammatory process, there is swelling of the affected gland, overlying pain, gland tenderness, fever, and on occasion difficulty in opening the mouth. Initial treatment should include rehydration oral antistaphylococcal antibiotic should be started while awaiting culture results. Hygiene and repeated massaging of the gland when tenderness had subsided. The present report describes a case of acute submandibular sialadenitis in a 70-year-old female.